The legitimacy of the Security Council in the humanitarian step in Syria (Al-MAHAD Journal, 2023)
The international humanitarian intervention in Syria portrays the protection of civilians in armed conflicts and the overall international humanitarian law, especially the concerns of the security council which aims to reduce human rights violations suffered by the Syrian people. The difference between the definitions is that there are multiple reasons for maintaining international peace and security or humanitarian reasons that is, excessive violence against civilians and subsequent arbitrary arrests mass killings and displacement. Supporters and opponents have different views on international humanitarian intervention. As for the increase of the suffering of the Syrian people the security council is left with the problematic presence of coercion that limits the international humanitarian intervention, especially the sovereignty of the state and under the internal jurisdiction of the hand, and justifies the exclusion contained in the text of article 2/7 of the UN charter, which authorized intervention under chapter VII of the order to alleviate the suffering of the Syrian people as aresult of human rights violations.